Estudo da estabilidade a campo dos pesticidas carbofurano e quincloraque em água de lavoura de arroz irrigado empregando SPE e HPLC-DAD - Peixoto, Sandra Cadore (2007)
The use of pesticides to control pests, diseases and weeds in crops of agricultural interest aims at the increase of production. The degradation of applied compounds or their conversion into other products, does not necessarily mean the loss of biological activity, and many times, this conversion can result in even more toxic and active products. The study of the pesticides persistence in crops is of great importance in order to evaluate the risks of environmental contamination. In this study, an analytical method for the residual determination of the insecticide carbofuran and the herbicide quinclorac in the water of irrigated rice farming, using SPE and HPLC-DAD, was developed and validated. The method consists of the pre-concentration of the water samples in SPE cartridges with 500 mg of C18 followed by elution with methanol. The extracts were analyzed by HPLC-DAD with a Gemini C18 column and detection at 220 nm for carbofuran and 270 nm for quinclorac. In the method validation, LOD, LOQ, linearity, precision (repeatability and intermediate precision) and accuracy (from the recovery) were evaluated. The LOQ values for the method were 2 μg L-1 for carbofuran and 0.6 μg L-1 for quinclorac. The analytical curves presented linearity between 0.5 and 10.0 mg L-1 for carbofuran and 0.05 and 10.0 mg L-1 for quinclorac, with coefficient of determination values higher than 0.995. The method presented good precision, with RSD values lower than 17.1%, and good accuracy, with recoveries between 82 and 112%. The detection by diode array allowed an adequate confirmation and quantification of the pesticides in study. After validation, the method was applied to analyze samples of water from irrigated rice crops from an experiment carried out at the Campus of the UFSM, where the pesticides, carbofuran and quinclorac, were applied, separately, in the 2006/2007 harvests. The herbicide quinclorac presented greater persistence, with a half life time of approximately 12 days, and residues were found up to 42 days after the application. The insecticide carbofuran was well less persistent, observing residues only up to 5 days after application. For carbofuran, it was not possible to determine the half life time and its metabolite, 3-hydroxycarbofuran, was not found in the samples analyzed.